Examiner and Judge Designs in Economics: A Practitioner's Guide - Eric Chyn; Brigham R. Frandsen; Emily Leslie (Institute of Labor Economics (IZA), 2025)
This article provides empirical researchers with an introduction and guide to research designs based on variation in judge and examiner tendencies to administer treatments or other interventions. We review the basic theory behind the research design, outline the assumptions under which the design identifies causal effects, describe empirical tests of the conditions for identification, and discuss tradeoffs associated with choices researchers must make for estimation. We demonstrate concepts and best practices concretely in an empirical case study that uses an examiner tendency research design to study the effects of pre-trial detention.
Keywords: C21; C26; C31; K14; C54; 330; judges; examiners; judge fixed effects; applied econometrics